The specificity of human nature in relation to other animals in Aristotelian thought - Mariz, Débora (Argumentos - Revista de Filosofia, 2014)
This article analyze to what extent human nature is distinguished from other animals, through the biological works of Aristotle as well as his Ethics. Our target, in this perspective, is analyze the psychophysiological mechanism of the action of animals. We understand that human nature is not fully determined and it is the condition of possibility that makes the man become accomplished, achieving its ultimate purpose.